A classification of online bidders in a private value auction: evidence from eBay. (13th August 2007) - Hou, Jianwei; Rego, Cesar
In traditional auctions, it is often assumed that bidders are a homogenous group. However, since most online bidders are average consumers instead of professional bidders, we suspect that online bidders are a heterogeneous group. The purpose of this paper is to explore the types of online bidders based on their real bidding behaviour in the context of consumer-to-consumer online auction market. A cluster analysis is employed and four types of online bidders are finally identified in a private value auction, namely, goal-driven bidders, experiential bidders, focused bidders, and opportunistic bidders. The profile and performance of each group are also discussed.